Dog Man : a tale of two kitties - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2017)
"Canine cop Dog Man is back, and he's about to be bested by the world's most conniving cat crook!"--
At head of title: Tree-House Comix proudly presents.
Keywords: Graphic novels; Dogs -- Fiction; Cats -- Fiction; Police -- Fiction; Humorous stories; Graphic novels